Biosensors for Studying Neuronal Proteostasis - Dudanova, Irina (Frontiers in Molecular Neuroscience, 2022)
Cellular health depends on the integrity and functionality of the proteome. Each cell is equipped with a protein quality control machinery that maintains protein homeostasis (proteostasis) by helping proteins adopt and keep their native structure, and ensuring degradation of damaged proteins. Postmitotic cells such as neurons are especially vulnerable to disturbances of proteostasis. Defects of protein quality control occur in aging, and have been linked to several disorders, including neurodegenerative diseases. However, the exact nature and time course of such disturbances in the context of brain diseases remain poorly understood. Sensors that allow visualization and quantitative analysis of proteostasis capacity in neurons are essential for gaining a better understanding of disease mechanisms and for testing potential therapies. Here, I provide an overview of biosensors developed for assessing the functionality of the neuronal proteostasis network, point out the advantages and limitations of different sensors, and outline their potential for biological discoveries and translational applications.